Parent Rated Symptoms of Inattention in Childhood Predict High School Academic Achievement Across Two Culturally and Diagnostically Diverse Samples - Lundervold, Astri J.; Meza, Jocelyn I.; Hysing, Mari; Hinshaw, Stephen P. (Frontiers in Psychology, 2017)
Objective: To investigate parent reports of childhood symptoms of inattention as a predictor of adolescent academic achievement, taking into account the impact of the child’s intellectual functioning, in two diagnostically and culturally diverse samples. Method: Samples: (a) an all-female sample in the U.S. predominated by youth with ADHD (Berkeley Girls with ADHD Longitudinal Study [BGALS], N = 202), and (b) a mixed-sex sample recruited from a Norwegian population-based sample (the Bergen Child Study [BCS], N = 93). Inattention and intellectual function were assessed via the same measures in the two samples; academic achievement scores during and beyond high school and demographic covariates were country-specific. Results: Childhood inattention predicted subsequent academic achievement in both samples, with a somewhat stronger effect in the BGALS sample, which included a large subgroup of children with ADHD. Intellectual function was another strong predictor, but the effect of early inattention remained statistically significant in both samples when intellectual function was covaried. Conclusion: The effect of early indicators of inattention on future academic success was robust across the two samples. These results support the use of remediation procedures broadly applied. Future longitudinal multicenter studies with pre-planned common inclusion criteria should be performed to increase our understanding of the importance of inattention in primary school children for concurrent and prospective functioning.